2014
DOI: 10.1167/iovs.13-13494
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin Knockdown Decreases Corneal Opacity

Abstract: PURPOSE. Wound induced corneal fibrosis can lead to permanent visual impairment. Keratocyte activation and differentiation play a key role in fibrosis, and vimentin, a major structural type III intermediate filament, is a required component of this process. The purpose of our study was to develop a nonviral therapeutic strategy for treating corneal fibrosis in which we targeted the knockdown of vimentin. METHODS.To determine the duration of plasmid expression in corneal keratocytes, we injected a naked plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…1 C). After corneal damage, corneal stromal cell fibrosis is the main cause of visual impairment, 17 so the level of α-smooth muscle actin (ɑ-SMA) in the cornea was measured by Western blot assay. The results showed that the protein level of ɑ-SMA in the cornea of rabbits with alkali burn was significantly reduced after S100A4 silencing (all P < 0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 C). After corneal damage, corneal stromal cell fibrosis is the main cause of visual impairment, 17 so the level of α-smooth muscle actin (ɑ-SMA) in the cornea was measured by Western blot assay. The results showed that the protein level of ɑ-SMA in the cornea of rabbits with alkali burn was significantly reduced after S100A4 silencing (all P < 0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HNE, 15-deoxy-Δ 12 14 -prostaglandin J 2 (15d-PGJ 2 ), prostaglandin A 1 (PGA 1 ) and their biotinylated derivatives were from Cayman Chemical. Diamide, DBB, Iac-B, TPEN, Z-LLL o MG132, Zinquin acid and Zinquin ethyl ester, anti-actin, anti-tubulin and anti-vimentin antibodies were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Previously considered as a marker for epithelial–mesenchymal transition, it is now recognized as an active factor in this process, and therefore in cancer cell dissemination 8 9 . Vimentin is essential in wound healing, but it can also promote excessive scarring 10 11 12 . Moreover, it plays a facilitating role in certain viral infections 13 14 and as an autoantigen in the pathogenesis of rheumatic fever 15 and rheumatoid arthritis 16 .…”
mentioning
confidence: 99%
“…A lack of vimentin is associated with defects in wound healing (12). Inhibiting vimentin protects from fibrotic injuries (13,14), whereas overexpression of vimentin promotes increased invasiveness and excessive scarring (10). Our previous studies have demonstrated that modified forms of vimentin target signaling pathways that include transcription of profibrotic genes in pulmonary fibrosis (15,16).…”
Section: Introductionmentioning
confidence: 99%